Bibliography of Rusûhî İsmâil Ankaravî - Ömer Gök (Ankara Araştırmaları Dergisi, 2016)
When we look at the history of Turkish civilization, it comes to our attention that certain authors have produced enormous canons of work. One of these particularly prolific authors is İsmâil Ankaravî. Also known by his pen name Rusûhî, İsmâil Ankaravî Effendi was initiated into the Mawlawi Order, becoming the sheikh of the Galata Mawlawi House for a long time and one of the important names in this tradition. In particular, he received the title of “Hazret-i Şârih” for his commentary on Masnavi, which became widely known. However, he also wrote many other works. This study aims to present past academic research (books, dissertations, articles, papers etc.) on Ankaravî’s works as a whole in order to help future researchers.